Strengthening the Buddhist Community Economy Through the Development of Sustainable Durian Plantations Based on Religious Values - Urip Widodo; Hendrikusi Maku; Mujiyanto Mujiyanto; Arina Afiyati Shadikah; Daulat Nathanael Banjarnahor (Marsiurupan: Journal of Community Development and Empowerment, 2026)
This community service activity aims to strengthen the economic capacity of the Buddhist community in Karang Village, Wonogiri Regency, through the development of sustainable durian plantations integrated with spiritual values. The program was specifically designed to address four key issues: limited technical knowledge in cultivation, low land productivity, inadequate business management, and poor market access. The implementation methodology utilized a Participatory Action Research (PAR) approach, encompassing initial situation analysis, intensive technical training (cultivation, Agroforestry), institutional mentoring for farmer groups, business management reinforcement, and comprehensive evaluation through pre- and post-tests and field observations. The results demonstrate a significant increase in technical knowledge (the average participant score rose from 46.5 to 83.2), enhanced crop productivity (seedling survival rate reached 93%), and a substantial reduction in production costs up to 85% through the adoption of self-produced organic fertilizers. Financially, the average monthly income from the agricultural sector increased from IDR 1,400,000 to IDR 2,350,000.